Potential Effects of Urban Contact Varieties in Teaching Home Language: A Case Study of Setswana Home Language Teachers - Botlholo, Koketso; Makgato, Mary Moshidi (Journal of Languages and Language Teaching, 2025)
This study explores the impact of urban contact varieties (UCVs) on the teaching of Setswana Home Language (HL) in Grade 10, focusing on the interference of UCVs and strategies to enhance. The study was conducted at two high schools where four participants were selected two Setswana educators from each school. The study employed a qualitative method. In this regard, four Setswana educators were interviewed.The qualitative approach aimed to expand and strengthen data collection. This article examines the potential effects of urban contact varieties (UCVs) on teaching Grade 10 learners at the two selected high schools in Winterveldt speaking and writing Setswana. The motivation for the research arose because of the observations made during the researcher`s years of study in one of the high schools and as one of the residents of Winterveldt. These observations suggest that teachers use UCVs to communicate at home and at school instead of the standard Setswana. As a result, many learners tend to perform poorly in Setswana Home Language (HL) and fail when they do not attain the required marks in their exams, mainly because they fail their home language subject because they are taught in UCVs.